Cytotoxicity and Cell Cycle Analysis of Asparagus Laricinus Burch. and Senecio Asperulus DC. on Breast and Prostate Cancer Cell Lines - Mfengwana, P.H.; Mashele, S.S.; Manduna, I.T. (Heliyon, 2019)
Aims: Medicinal plants play an important role in our African communities for treatment and prevention of various diseases including cancer. This study was aimed on evaluating the cytotoxicity activities of Asparagus laricinus Burch. and Senecio asperulus DC. Main methods: In vitro cytotoxicity screening was carried out using fluorescent cellular stains on human prostate cancer (PC3), human breast cancer (MCF-7) and the non-cancerous African green monkey kidney (Vero) cell lines. The cells were imaged with the ImageXpress Micro XLS Widefield fluorescent Microscope, and the acquired images were analysed using the MetaXpress software and the Multi-Wavelength cell scoring application module. Melphalan was used as a positive control in all experiments. Key findings: Asparagus laricinus methanol and Senecio asperulus DC. dichloromethane extracts exhibited cytotoxicity activity against breast cancer cells with IC50 values of 97.6 μg/mL and 69.15 μg/mL, respectively. Cell cycle analysis suggested that Asparagus laricinus methanol extract induced cell death selectively through apoptosis observed from Annexin V-FITC and PI stain. Cell cycle analysis also showed that Senecio asperulus DC. dichloromethane extracts induced breast cancer cells death through cell arrest at the synthesis phase and G2 phase. Senecio asperulus DC. dichloromethane extracts further showed cytotoxicity activity against prostate cancer cells with IC50 values of 69.25 μg/mL due to cell arrest at the G2 and early mitotic (G2/M) phase. Significance: We, therefore, propose that the methanol extract of Asparagus laricinus is a suitable aspirant for future breast cancer chemotherapeutic drug, due to its selective cytotoxicity on cancer cells and not on non-cancerous cells.
Published Article
Keywords: Cancer Research; Natural Product Chemistry; Biochemistry; Cell Biology